Mycoviruses in the Plant Pathogen Ustilaginoidea virens Are Not Correlated with the Genetic Backgrounds of Its Hosts - Zhong, Jie (Int J Mol Sci, 2017)
Ustilaginoidea virens, the causal agent of rice false smut, is one of the most devastating grain diseases that causes loss of yield in most rice-growing areas worldwide. In this study, we performed a dsRNA screen to isolate mycoviruses from 35 U. virens strains. The results revealed that 34 of the tested isolates were infected by various dsRNA elements, displaying highly viral diversity and mixed infections. We characterized a 5.3 kbp dsRNA from a typical isolate containing dsRNA segments with sizes ranging from 0.5 to 5.3 kbp. Sequence analysis of its genomic properties indicated that it is a novel victorivirus, named Ustilaginoidea virens RNA virus 5 (UvRV5), that belongs to the family Totiviridae. RT-PCR detection was performed and indicated that not all the dsRNA bands that were 5.3 kbp in size contained UvRV5. Moreover, the genetic relatedness of all the U. virens strains was estimated according to phylogenetic analysis of the partial intergenic spacer region (IGS) sequences. However, concordance was not found between the dsRNA profiles and the IGS-based genetic relatedness of their host fungi.